Simultaneous Evaluation of Multiple I/O Strategies - Gonzalez-Ferez, Pilar; Piernas, Juan; Cortes, Toni (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2010)
We present a framework for simulating the performance obtained by different I/O system mechanisms and algorithms at the same time, and for dynamically turning them on and off to improve the overall system performance. A key element of this framework is the the design and implementation of a virtual disk inside the Linux kernel. Our virtual disk creates a virtual block device which is able to simulate any hard drive with a negligible overhead, without interfering with regular I/O requests. We describe the potential of our proposal in REDCAP, a RAM-based disk cache which is dynamically activated/deactivated according to the throughput achieved. The results show that, by using our virtual disk, REDCAP obtains its maximum possible improvements: up to 80% for workloads with some spatial locality, and the same performance as a ''normal system" for workloads with random or large sequential reads.